Media reporting of corruption: policy implications - Masters, Adam B. (Crime, law and social change, 2015)
Are policy responses related to experiences or perceptions of corruption? This article examines newspaper reporting of corruption in an Australian jurisdiction and compares these with perceptions of corruption and experiences of corruption in the community. The policy challenge is to understand the gaps between media reporting about corruption, the perceptions of corruption they help generate and peoples concrete experiences of corruption. Research cited in this article shows that corruption tends to be perceived at a higher level than the evidence would suggest in both high income and low income countries. Such perceptions have policy relevance as they can shape the structure of national integrity systems. This leads to our research question: how does the media portray corruption and asks whether policy responses are related to experiences or perceptions of corruption? The lessons here can be applied in other jurisdictions.